Demographical Variations of Sensory Neural Hearing Loss (SNHL) in Chronic Suppurative Otitis Media (CSOM) patients at JPMC Karachi - Zubair Anwar, Saad Abdur Rehman Afaque, Muhammad Imran Bhatti, Muhammad Razzaq Dogar, Maria Mahmood, Adnan Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: CSOM is significantly associated with SNHL but with mixed demographical associations being reported in literature.To determine the demographical variations (age and gender) of SNHL among CSOM patients Study design and setting: Cross-sectional observational study at Jinnah Postgraduate Medical Center, Karachi, Pakistan. Methodology: Using non-probability convenient sampling, diagnosed CSOM patients within six months between 10-50 years and of either gender were included while patients with history of SNHL previously of using ototoxic drugs, ear trauma or refusing to consent were excluded. SPSS v23.0 was used for analysis of data and chi-square was applied keeping p-value <0.05 as statistically significant. Results: From total 200 patients,60 (30%) patients were between 10-18 years, 120 (60%) between 19-35 years and 35-50 years were 20 (10%) patients. 145 (72.5%) were females while 55 (27.5%) males. SNHL was observed in 36 (18%) of patients. Between 10-18 years age group, 10 (16.7%) patients were reported with SNHL, between 19-35 years age group 22 (18.3%) while between 35-50 years, 4 (20%) of patients were found to have SNHL with an insignificant p-value of 0.934. 28 (19.3%) males were reported to have SNHL while 8 (14.5%) females were observed to have SNHL with CSOM. An insignificant p-value of p-0.434 was reported between the genders. Conclusion: According to the results of this study, SNHL was insignificantly associated with CSOM according to demographics (age and gender). Further studies are required to validate the findings of this study. Keywords: Chronic Suppurative Otitis Media, Sensori Neural Hearing Loss, Otitis Media